The Feminine Element of Nature Creation from Ibn Arabi's Perspective - Qosdana, M. Fatih; Muzadi, Ulya Aslam (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This research examines feminine elements in Ibn ‘Arabī's cosmology and their implications for ecofeminism and contemporary Islamic feminism. It responds to the lack of holistic studies that integrate Ibn ’Arabī's Sufi metaphysical thought with Islamic feminist and ecological discourse. The research method used is a descriptive-analytical approach by studying primary texts by Ibn ‘Arabī and secondary literature related to Islamic feminism and ecofeminism. The study results reveal that Ibn ’Arabī views femininity as a symbol and an essential and equal aspect of divine reality, opening up spiritual and social space for gender equality. The concept of femininity in Ibn ‘Arabī's Sufi cosmology serves as a strong and relevant theological foundation for contemporary Muslim feminists and an important basis for the development of Islamic ecofeminism. This research contributes to more inclusive, progressive, and sustainable studies of gender and spirituality in Islam.